The nexus of faith and resistance: religious elements in Mahmoud Darwish's poetry - Altabaa, Homam; Azmi, Nurul Nabihah (International Islamic University Malaysia, 2024)
Palestinian poetry portrays the multifaceted experiences of Palestinians following the Israeli occupation in 1948. The works of Mahmoud Darwish are prominent as they embody the pain, resilience and resistance of Palestinians. The use of religious elements to frame their struggles is common in the works of Palestinian poets, including Mahmoud Darwish. However, there are not any specific studies that focus on religious elements in his distinguished poetry collection, Lesser Roses (1986). In this study, religious elements in selected poems in the Lesser Roses collection are analysed to add a new dimension to the field of postcolonial literature as well as to the research of Palestinian poetry by looking at the significance of religious elements in the poems and how they are used to convey unique Palestinian experiences. The analysis reveals that Darwish uses religious elements from the narrative and ritual religious dimensions to portray exile, dislocation, and counter-discourse in the poems. The poet adapts various religious elements from multiple faiths to convey the themes of suffering and resistance that resonate with Palestinians’ struggles.